Synthesis and structural characterisation of metal-organic frameworks composed of transition or lanthanide metal cations linded via tritopic ligands - Tobin, Gerard Martin (Trinity College (Dublin, Ireland). School of Chemistry, 2014)
The work presented in this thesis is concerned with the design and synthesis of metal- organic frameworks (MOFs). MOFs are a class of hybrid inorganic-organic material composed of metal-ions or clusters of metal-ions linked via organic linkers into high dimensional frameworks. Interest in MOFs arises from their advantageous physicochemical properties such as porosity and ease of functionalisation, which facilitate their use in a diverse range of potential applications such as energy storage, drug delivery and catalysis.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin